IN VITRO ANTIOXIDANT POTENTIAL AND HEPATOPROTECTIVE ACTIVITY OF TAXUS WALLICHIANA - Bhat, Muzafar Ahmad; Ganie, Showkat Ahmad; Dar, Khalid Bashir; Ali, Rohaya; Hamid, Rabia (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Taxus wallichiana, the member of family Taxaceae is used for the cure of various ailments by a large ethnic population native to the forests in Kashmir valley. The aim of this study is to evaluate antioxidant potential and hepatoprotective action of T. wallichiana as claimed by the ethnic population segment. Methods: Antioxidant potential of different T. wallichiana extracts was evaluated by estimating the total phenolics, 1,1-diphenyl -2-picrylhydrazyl (DPPH), reducing power, microsomal lipid peroxidation (LPO), and hydroxyl radical scavenging activity through standard protocols. Hepatoprotective activity of T. wallichiana was determined by evaluation of liver marker enzyme (aspartate transaminase, alanine transaminase, and alkaline phosphatase) levels using standard protocols and by histological analysis of rat liver tissues of different animal groups against CCl4 induced liver damage. Results: Phenolic content expressed as gallic acid equivalents (GAE/g) was found maximum in case of ethanolic extract (153.34 mg GAE/g), followed by extracts of methanol (149.24 mg GAE/g), hexane (134 mg GAE/g), ethyl acetate (128.9 mg GAE/g), chloroform (121.37 mg GAE/g), and aqueous (113.00 mg GAE/g). At concentration of 700 Î¼g/ml, DPPH radical scavenging activity of methanol extract was 88.29% with IC50 (212.00 Î¼g/ml), aqueous (82.47%) with IC50 (258.29 Î¼g/ml), and ethyl acetate (79.57%) with IC50 (301.80%Î¼g/ml). The reducing power of the extracts increased in a concentration dependent manner. At concentration of 700 Î¼g/ml, 79%, 68%, and 56% inhibition was observed with extracts of methanol, aqueous, and ethyl acetate on microsomal LPO with IC50 values of 126.09, 168.83, and151.96 Î¼g/ml, respectively. Superoxide radical scavenging activity of T. wallichiana extracts increased in a dose-dependent manner with IC50 values 170.30 Î¼g/ml (methanol), 257.00 Î¼g/ml (aqueous), and 297.55 Î¼g/ml ethyl acetate extract. T. wallichiana extracts exhibited antioxidant effects on calf thymus DNA damage. The results further depict the hepatoprotective action of T. wallichiana extract at doses of 100 and 300 mg/kg and were comparable with that of standard treatment comprising 50 mg/kg-day of Vitamin C, a known hepatoprotective agent. The data were substantiated with histopathological studies of rat liver sections. Conclusion: These results comprehensively depict that T. wallichiana extracts are endowed with the free radical sequestering potential and be employed as potential antioxidant and hepatoprotective arsenal against many oxidative stress linked diseases.Â 